Educational Leadership and Management in Diverse and Complex Situations: Opportunities and Challenges in Nepal and Indonesia (OCEM Journal of Management, Technology & Social Sciences, 2026)
This study presents a comparative analysis of educational leadership and management practices in Nepal and Indonesia, systematically reviewing 48 articles to examine how diverse socio-cultural, institutional, and political contexts influence leadership effectiveness in resource-constrained settings. The research investigates the adoption and outcomes of models like transformational, visionary, servant, and spiritual leadership across both nations.Findings indicate that although styles such as transformational and distributed leadership positively affect teacher motivation, school culture, and innovation, their practical implementation is hindered by significant systemic barriers. These obstacles include pervasive bureaucratic centralization, recurrent political interference in educational affairs, and a severe lack of structured professional development opportunities for leaders. The research also reveals a critical gap in validated, context-specific leadership frameworks, particularly within vocational and religious educational institutions in both countries.Leadership efficacy is highly context-dependent: in Nepal. In ethical and affiliative leadership, often employed by female principals, fosters strong relational environments. In contrast, Indonesian leadership practices are deeply guided by local wisdom, emphasizing ethical and participatory governance. The study ultimately highlights a persistent research-practice gap, noting a lack of empirical evidence linking current leadership models directly to long-term student learning outcomes or institutional development. It concludes by advocating a shift away from procedural managerialism towards a morally grounded, pedagogically responsive, and culturally informed approach.